Implementation of Application for Change of Name Due to Change of Religion Based on Law Number 24 of 2013 concerning Population Administration (Study of Stipulation: District Court of Cibinong Number 87/Pdt.P/2024 PN Cbi) - Suci Fatara Adhwa; Latifah Ratnawaty; Annisa Aminda (Universitas Ibn Khaldun Bogor, 2026)
The application for name change due to religious conversion based on the Stipulation of Cibinong District Court Number 87/Pdt.P/2024/PN Cbi was filed by the applicant who wanted to change his name from Christian to a name that reflected his new identity as a Muslim, in line with his decision to embrace Islam. This name change was filed through a voluntary petition because it did not involve other parties who were legally disadvantaged. This study aims to analyze the procedure based on the population administration law and the extent to which the state provides protection for the right to identity and freedom of religion in the name change process. and to find out the legal considerations of judges in determining name changes due to religious conversion. The method used is normative juridical with statutory approach and case study. The results of the study show that the name change application must be based on a court decision as stipulated in Article 52 of Law Number 23 of 2006 concerning Population Administration which has been amended to Law Number 24 of 2013. The stipulation confirms that the positive law in Indonesia provides space and protection for the expression of beliefs through changes in legal identity, as long as it is done according to legal procedures. The state is obliged to respect and facilitate it as a form of juridical recognition of the personal rights of citizens to live life in accordance with their beliefs. This process also reflects the role of the judiciary in maintaining the balance between legal certainty, administrative order, and respect for human rights within the framework of the national legal system.